Extra-legal power and legitimacy : perspectives on prerogative - Fatovic, Clement, 1973-; Kleinerman, Benjamin A. (New York : Oxford University Press, 2014)
This title examines the costs and benefits associated with different ways that governments have wielded extra-legal powers in times of emergency. It surveys distinct models of emergency governments and draw diverse and conflicting approaches by joining influential thinkers into conversation with one another.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on December 2, 2013).
Keywords: War and emergency powers -- United States; War and emergency powers